Electrodeposition of High-Surface-Area IrO2 Films on Ti Felt as an Efficient Catalyst for the Oxygen Evolution Reaction - Park, Yu Jin; Lee, Jooyoung; Park, Yoo Sei; Yang, Juchan; Jang, Myeong Je; Jeong, Jaehoon; Choe, Seunghoe; Lee, Jung Woo; Kwon, Jung-Dae; Choi, Sung Mook (Frontiers in Chemistry, 2020)
Under acidic conditions, IrO2 exhibits high catalytic activity with respect to the oxygen evolution reaction (OER). However, the practical application of Ir-based catalysts is significantly limited owing to their high cost in addition to the scarcity of the metal. Therefore, it is necessary to improve the efficiency of the utilization of such catalysts. In this study, IrO2-coated Ti felt (IrO2/Ti) electrodes were prepared as high-efficiency catalysts for the OER under acidic conditions. By controlling the surface roughness of the Ti substrate via wet etching, the optimum Ti substrate surface area for application in the IrO2/Ti electrode was determined. Additionally, the IrO2 film that was electrodeposited on the 30 min etched Ti felt had a large surface area and a uniform morphology. Furthermore, there were no micro-cracks and the electrode obtained (IrO2/Ti-30) exhibited superior catalytic performance with respect to the OER, with a mass activity of 362.3 A gIr-1 at a potential of 2.0 V (vs. RHE) despite the low Ir loading (0.2 mg cm-2). Therefore, this proposed strategy for the development of IrO2/Ti electrodes with substrate surface control via wet etching has potential for application in the improvement of the efficiency of catalyst utilization with respect to the OER.